Comparison of The Efficacy of Intravenous Norepinephrine and Phenylephrine as Vasopressor Agents in The Management of Septic Shock in ICU Patients at Haji Adam Malik General Hospital Using Lactate and Stroke Volume Variation Indicators - Fandy Faidhul Attamimi; Dadik Wahyu Wijaya; Qadri Fauzi Tanjung; Rina Amelia (JAI (Jurnal Anestesiologi Indonesia), 2026)
Background: Septic shock is a life-threatening complication of sepsis, characterized by refractory hypotension and tissue hypoperfusion, requiring rapid vasopressor therapy. Norepinephrine is the drug of choice, but phenylephrine is still used in certain conditions, such as tachyarrhythmia or high output. Evidence comparing the effectiveness of the two is still limited, especially in Indonesian ICUs. Therefore, this study assessed the efficacy of norepinephrine and phenylephrine using lactate clearance and stroke volume variation (SVV) as indicators of perfusion and hemodynamic response in the intensive care unit (ICU) of Adam Malik General Hospital, Medan.Methods: This study was a prospective, double-blind, randomized controlled clinical trial conducted in the ICU of Adam Malik General Hospital, Medan, involving 32 adult patients (aged 18–65 years) with septic shock, as defined by the Sepsis-3 criteria. Patients were randomly assigned to two groups receiving norepinephrine infusion (n = 16) or phenylephrine infusion (n = 16) as the primary vasopressor. Lactate levels and SVV were measured at baseline (T0) and 6 hours after therapy (T1). The primary outcome was the change in lactate and SVV, with analysis using paired and independent t-tests at a significance level of p < 0.05.Results: 32 patients were divided into two groups, each with 16 patients receiving norepinephrine or phenylephrine. After 6 hours of therapy, norepinephrine reduced lactate levels from 8.41±1.88 to 5.76±1.99 mmol/L and SVV from 14.25±2.17 to 8.18±1.90 mmHg (p<0.001). Phenylephrine also reduced lactate from 7.40±1.77 to 6.70±1.77 mmol/L and SVV from 15.93±2.56 to 12.50±2.63 mmHg (p<0.001).Conclusions: Intravenous norepinephrine is more effective than phenylephrine in lowering lactate and improving SVV in septic shock patients in the ICU, thus supporting its use as the primary vasopressor. Phenylephrine remains an alternative with close hemodynamic monitoring. Further studies are needed to confirm these findings and understand the mechanism behind the difference in effectiveness between the two.